2020
DOI: 10.1186/s12913-020-05568-w
|View full text |Cite
|
Sign up to set email alerts
|

The current landscape of pre-exposure prophylaxis service delivery models for HIV prevention: a scoping review

Abstract: Background: Strengthening HIV prevention is imperative given the continued high HIV incidence worldwide. The introduction of oral PrEP as a new biomedical HIV prevention tool can be a potential game changer because of its high clinical efficacy and the feasibility of its provision to different key populations. Documenting the existing experience with PrEP service delivery in a variety of real-world settings will inform how its uptake and usage can be maximised. Methods: We conducted a scoping review using the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 58 publications
2
37
1
Order By: Relevance
“…The unique situation of reduced physical contact and a societal lockdown may be a good opportunity to consider alternative forms of PrEP follow-up and sexual health services, such as online counselling or home-based sampling. 22 Additionally, we suggest further research is needed to investigate what minimum package for PrEP follow-up would be feasible and for whom. Those who had sex with non-steady partners during the lockdown in our sample were more likely to have engaged in group sex, chemsex or sex work before the lockdown.…”
Section: Discussionmentioning
confidence: 99%
“…The unique situation of reduced physical contact and a societal lockdown may be a good opportunity to consider alternative forms of PrEP follow-up and sexual health services, such as online counselling or home-based sampling. 22 Additionally, we suggest further research is needed to investigate what minimum package for PrEP follow-up would be feasible and for whom. Those who had sex with non-steady partners during the lockdown in our sample were more likely to have engaged in group sex, chemsex or sex work before the lockdown.…”
Section: Discussionmentioning
confidence: 99%
“…In the nearly 10 years since clinical trials confirmed the safety and efficacy of pre-exposure prophylaxis (PrEP) for HIV prevention, diverse PrEP delivery models have been implemented around the world, primarily in high-income settings [1,2]. In the U.S., home to the world's largest number of PrEP users, PrEP is delivered through a variety of clinic-based, pharmacy-based, and telehealth models [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…21 Nurse-led PrEP delivery models have been used in numerous international settings. 5,[28][29][30] Prior to PrEP, nurses already played a crucial role in HIV services in Australia. 31 In the context of PrEP, nurse-led models were instrumental to the rapid enrolment of participants in Australian PrEP demonstration studies.…”
Section: Introductionmentioning
confidence: 99%